Legal Protection of the Rights of Women Workers in Sidoarjo Regency: Perlindungan Hukum Hak Pekerja Perempuan Di Kabupaten Sidoarjo - Andriani, Lia; Phahlevy, Rifqi Ridhlo (Universitas Muhammadiyah Sidoarjo, 2022)
Increased economic growth and the number of new industries resulted in the expansion of employment opportunities for both men and women, and did not prioritize job skills requirements that specifically attracted women to work. In modern times, female workers are more dominant than male workers. Workers should get legal protection to guarantee and protect their rights as workers. Workers' protection itself is regulated in Law No. 13 of 2003 which was changed to Law No. 11 of 2021 on Job Creation. The Sidoarjo regional government should monitor and supervise the implementation of laws that protect the rights of women workers in Sidoarjo so that it can be known and assessed whether the implementation of the applicable laws is appropriate or not, and efforts can be made to increase legal protection if it is not appropriate.